In vitro study on the hemocompatibility of plasma electrolytic oxidation coatings on titanium substrates. Issue 4 (5th December 2019) - Klein, Mario; Kuhn, Yasmin; Woelke, Eva; Linde, Torsten; Ptock, Christoph; Kopp, Alexander; Bletek, Thomas; Schmitz‐Rode, Thomas; Steinseifer, Ulrich; Arens, Jutta; Clauser, Johanna C.
Abstract: Passively levitated ventricular assist devices (VADs) are vulnerable to impeller‐housing contact and could benefit from surface coatings that improve wear resistance. Such coatings can be manufactured by plasma electrolytic oxidation (PEO), but their suitability for blood‐contact applications needs further investigation. We therefore compared blood–surface interactions of polished titanium grade 5 (Ti Gr 5), as a general VAD reference material, uncoated ground titanium grade 4 (Ti Gr 4) and two commercially available PEO coatings on Ti Gr 4. In n  = 4 static platelet adhesion tests, material samples were incubated with platelet‐rich plasma (PRP) and consecutively analyzed for adhesive platelets by immunofluorescence microscopy. Additionally, PRP supernatant of incubated material samples was analyzed for changes in antithrombin III and fibrinogen concentrations by turbodimetry and enzyme‐linked immunosorbent assay, respectively. We could not find any significant differences between the materials in the analyzed hemocompatibility markers ( P  > .05). Thus, we conclude that PEO coatings might offer a similar hemocompatibility to that of polished Ti Gr 5 and uncoated Ti Gr 4. Nevertheless, future studies should investigate blood–surface interactions of PEO coatings under realistic VAD‐related flow conditions to better evaluate their potential for VAD applications.